Work in times of Brexit: explanatory mechanisms linking macropolitical events with employee well-being. Issue 5 (3rd September 2022) - Schilbach, Miriam; Selenko, Eva; Baethge, Anja; Rigotti, Thomas
ABSTRACT: With this study, we examine work-related phenomena that may convey the relationship between a macropolitical event (i.e., Brexit) and personal well-being in a sample of UK-based academics. Drawing on transactional stress theory, we propose an appraisal-based mediation model. Specifically, we argue that cognitive appraisal of Brexit relates to job (in)security and the relationship quality with co-workers which represent indicators of the fundamental humgan needs for safety and belonging and thus, relate to personal well-being. We conducted a three-wave panel study, the final sample consisted of 115 individuals, and we used Bayesian path analysis to test the presumed hypotheses. Results revealed that academics in this sample predominantly appraised Brexit as threatening and less as challenging. As expected, threat appraisal related to more qualitative job insecurity and worse well-being. Further, deviating from communal appraisal (i.e., appraising Brexit as challenging) related to deteriorating relationship quality and lower well-being. Our findings illustrate the relevance of an appraisal-based perspective when researching controversial shared events. They further outline that cognitive appraisal likely occurs in a social context whereby challenge appraisal may entail a dark side when it indicates a deviation from peers' norms.